Numerical Investigation of Convective Heat Transfer and Fluid Flow Past a Three Square Cylinders Controlled by a Partition in Channel - Youssef Admi; Mohammed Amine Moussaoui; Ahmed Mezrhab (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
This document presents a research article on the control of fluid flow around three heated square cylinders placed side by side in a 2D horizontal channel using a flat plate. The objective of this research is to examine the effect of the position, length and height of a flat plate on fluid flow and heat transfer. For this purpose, numerical simulations are performed by using the Boltzmann double relaxation time multiple network method (DMRT-LBM). The MRT-D2Q9 and MRT-D2Q5 models are used to treat the flow and temperature fields respectively. In contrast to several existing investigations in the literature in this domain which study the passive control of the flow using a horizontal or vertical plate around a single cylinder, this work presents a numerical study on the effect of the position, length and height of a flat plate (horizontal and vertical) on three heated square cylinders on the flow and temperature fields. First, the effect of the position and length of the horizontal flat plate is examined. This study shows that the implementation of a flat plate of length Lp = 4D at a position g=3 behind the central cylinder reduces the amplitude of the Von Karman Street and allows large and regular heat exchange. Thus, in the second part, the effect of the position and height of the vertical flat plate is studied. The results obtained show that the implementation of a flat plate of height h=2D at a position g=3 behind the central cylinder improves the thermal exchange between the incoming fluid and the heated cylinders. This numerical work could lead to the prediction of the cooling of the electronic components: The cooling of the obstacles is all the better when the control plate is arranged at g = 3 and its height h = 2D in the case of the vertical plate or its length Lp equal to 4D in the case where the plate is implemented horizontally